France: Equal Opportunity Vs. Selectivity - Sursock, Andrée (International Higher Education, 2024)
France focuses on students’ socioeconomic backgrounds to ensure equal opportunity. While the system remains unequal and results in social reproduction, there is a national consensus that efforts must be exerted to broaden access and improve the success of marginalized students.